Anion-cation doped modified cobalt-free lithium-rich manganese-based positive electrode material and preparation method thereof

The cobalt-free lithium-rich manganese-based cathode material prepared by the anion-cation doping modification method solves the problems of poor voltage attenuation and cyclic stability of existing materials, and achieves the effects of slowing down voltage attenuation, excellent cyclic performance and improved rate performance.

CN119390135AActive Publication Date: 2025-02-07WUHAN INST OF TECH +1

Patent Information

Application Number
CN202411378473.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing cobalt-free lithium-rich manganese-based cathode materials have problems of low efficiency, poor large-rate performance and poor cycle stability for the first time, especially the severe capacity and voltage attenuation under long cycles, which limits its commercial application.

Method used

By the anion and cation doping modification method, a modified lithium-rich manganese-based precursor was prepared by using metal salt solution, precipitant, fluorine source and complexing agent, and mixed ball milling and sintering with the lithium source to prepare Li1.2Mn ( 0.6-x)AlxNi0.2O(2-y)Fy type cobalt-free lithium-manganese-based positive electrode material.

Benefits of technology

The modified material has slowed down voltage attenuation, excellent cycle performance, improved first-round Coulomb efficiency and improved rate performance. It is suitable for fast-charging batteries, solving the problems of voltage attenuation and poor cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390135A_ABST
    Figure CN119390135A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a modified cobalt-free lithium-rich manganese-based positive electrode material doped with anions and cations and a preparation method of the modified cobalt-free lithium-rich manganese-based positive electrode material. According to the method, a modified lithium-rich manganese-based precursor is prepared from a metal salt solution, a precipitator, a fluorine source and a complexing agent, and the anion-cation co-doped cobalt-free lithium-rich manganese-based positive electrode material is prepared from the modified lithium-rich manganese-based precursor and a lithium source. The metal salt solution contains manganese salt, nickel salt and aluminum salt. According to the method, by doping Al and F, the voltage attenuation is effectively reduced, the long cycle performance of the material is improved, the rate capability of the material is improved, and in addition, mixed arrangement of lithium and nickel cations is effectively inhibited, so that the cycle stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to an anion- and cation-doped modified cobalt-free lithium-rich manganese-based positive electrode material and a preparation method thereof. Background Art

[0002] As the global demand for sustainable and clean energy continues to increase, lithium-ion batteries, as high-energy-density energy storage devices, play an increasingly important role in portable electronic devices, electric vehicles, and large-scale energy storage systems. 1.2 Mn 0.6 Ni 0.2 O2(LNMO) has become a hot topic in the field of lithium-ion batteries due to its high specific capacity, cost-effectiveness and environmental friendliness. This type of material has a capacity of more than 250mAh g -1 Theoretical capacity and over 900Whkg -1 It has an energy density of 1.5W and has a lower cost advantage than traditional positive electrode materials such as LiCoO2 and LiFePO4, which is of great significance for promoting the driving range of electric vehicles and reducing battery costs.

[0003] However, lithium-rich manganese-based cathode materials still have problems such as low initial coulombic efficiency, poor high-rate performance and poor cycle stability, as well as severe capacity and voltage decay under long cycles, which seriously limit their commercialization. Therefore, how to further suppress the average voltage decay of lithium-rich manganese-based cathode materials and improve the cycle stability of materials is the focus and difficulty of research in this field.

[0004] At present, some modification methods have improved the performance of LNMO to a certain extent, but these modification methods involve many types of doped metals, the corresponding effects are uneven, the doping process is complicated and the cost is high, and they cannot meet the demand for LNMO. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a cobalt-free lithium-rich manganese-based positive electrode material modified by anion and cation doping and a preparation method thereof.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] The present invention provides a method for preparing an anion- and cation-doped modified cobalt-free lithium-rich manganese-based positive electrode material, wherein a modified lithium-rich manganese-based precursor is prepared by using a metal salt solution, a precipitant, a fluorine source, and a complexing agent, and the anion- and cation-co-doped cobalt-free lithium-rich manganese-based positive electrode material is prepared by using the modified lithium-rich manganese-based precursor and a lithium source;

[0008] The metal salt solution contains manganese salt, nickel salt and aluminum salt; wherein the molar ratio of manganese, nickel and aluminum is a:b:x, and the molar ratio of fluorine is y; the value ranges of a, b, x and y are: a>0.5, 0<b≤0.2, 0<x<0.1, and a+b+x=0.8; 0.01≤y≤0.06.

[0009] Based on the above technical solution, the present invention can also be improved as follows.

[0010] Furthermore, the precipitant includes alkaline solution, and the complexing agent includes one or more of ammonia water and ammonium bicarbonate.

[0011] Furthermore, the lithium source is one or more of lithium hydroxide, lithium sulfide, and lithium carbonate; the aluminum salt is one or both of aluminum oxide and aluminum nitrate; and the fluorine source includes one or both of ammonium fluoride and lithium fluoride.

[0012] Further, the following steps are included:

[0013] S1, after dissolving the complexing agent, the metal salt solution, the precipitant and the fluorine source are injected into the base liquid in parallel as a base liquid, stirred and heated to carry out a coprecipitation reaction, and after the reaction is completed, cooled, filtered and dried to obtain the modified lithium-rich manganese-based precursor;

[0014] S2, mixing the modified cobalt-free lithium-rich manganese-based precursor with the lithium source, subjecting the mixture to ball milling treatment, and then sintering the mixture.

[0015] Furthermore, in step S1, the flow rate of the parallel flow injection is 30 to 80 ml / min.

[0016] Furthermore, in step S1, the pH of the coprecipitation reaction is 8 to 9, the reaction temperature is 50 to 80° C., and the reaction time is 8 to 16 hours.

[0017] Furthermore, in step S2, the sintering includes a first stage sintering and a second stage sintering in sequence; the first stage sintering has a holding time of 4 to 8 hours at a temperature of 400 to 600°C, and the second stage sintering has a holding time of 8 to 16 hours at a temperature of 750 to 950°C.

[0018] The present invention also provides a cobalt-free lithium-rich manganese-based positive electrode material modified by anion and cation doping, which is prepared by the above method; the chemical formula of the positive electrode material is Li 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) F y .

[0019] The present invention also provides a lithium-ion battery positive electrode plate, which is prepared by using the above-mentioned anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material.

[0020] The present invention also provides a lithium ion battery, comprising the lithium ion battery positive electrode sheet as described above.

[0021] The beneficial effects of the present invention are:

[0022] (1) The preparation method of the anion- and cation-doped modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention is to simultaneously perform anion- and cation-modification by doping Al and F; Al doping can adjust the local electronic structure, increase the redox potential, improve the interaction with oxygen, further stabilize the lattice oxygen and inhibit the release of lattice oxygen, so that the positive electrode material structure is stable and has good long cycle performance; F doping can induce the formation of an initial spinel phase on the surface of the material, while inhibiting the transformation of the material from a layered phase to a spinel phase during the cycle, thereby improving the conductivity of the material ions and electrons, and thus improving the rate performance of the material;

[0023] (2) The preparation method of the anion- and cation-doped modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention can slow down the voltage decay of the modified positive electrode material and improve the cycle performance, thereby solving the problems of severe voltage decay and poor cycle stability of the existing cobalt-free lithium-rich manganese-based positive electrode material;

[0024] (3) The preparation method of the anion-cation doped modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention adopts a coprecipitation method-high temperature solid phase method to synthesize a cobalt-free lithium-rich manganese-based positive electrode material with aluminum doped manganese and fluorine doped oxygen. The synthesis can follow the conventional lithium-rich manganese-based material preparation process. By co-doping aluminum and fluorine elements into the reaction solution, a lithium-rich manganese-based material with excellent electrochemical stability and performance can be obtained without large-scale addition of production processes and links. The method has a wide range of applications;

[0025] (4) The preparation method of the anion- and cation-doped modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention has a simple preparation process and is easy to control. The particle size of the positive electrode material can be controlled by controlling the pH value and the insulation time. The product has uniform particle size and excellent electrochemical performance, which meets various product requirements. The entire production process has less pollution, is relatively simple, has strong controllability, does not require advanced instruments, is low in cost, and is suitable for industrial production.

[0026] (5) The anion- and cation-doped modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention reduces the mixing of lithium and nickel cations, increases the interlayer spacing of the layered structure, improves stability, and achieves more convenient insertion and extraction of lithium ions. The electron transfer rate of the material is faster, thereby effectively improving the first-cycle coulomb efficiency and cycle stability of the material. After fluorine-aluminum doping, the rate performance is improved under 5C high current conditions, which is conducive to the application of the material in future fast-charging batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The preparation method of the anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention, the PXRD patterns of the materials of Example 8, Example 3 and Example 7;

[0028] Figure 2 The preparation method of the anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention, the SEM image of the material of Example 8, Figure 2 The scale bar in a is 400 nm. Figure 2 The scale bar in b is 100 nm;

[0029] Figure 3 The preparation method of the anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention, the SEM image of the material in Example 3, Figure 3 The scale bar in a is 400 nm. Figure 3 The scale bar in b is 200 nm;

[0030] Figure 4 The preparation method of the anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention, the SEM image of the material of Example 7, Figure 4 The scale bar in a is 400 nm. Figure 4 The scale bar in b is 200 nm;

[0031] Figure 5 This is a preparation method of anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention, and a comparison chart of the cycle performance of the materials of Example 8, Example 3 and Example 7;

[0032] Figure 6 This is a preparation method of anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention, and a first cycle charge and discharge comparison diagram of the materials of Example 8, Example 3 and Example 7;

[0033] Figure 7 This is a method for preparing anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention, and a rate performance comparison diagram of the materials of Example 8, Example 3 and Example 7;

[0034] Figure 8The preparation method of the anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention, the discharge curve diagram of Example 8 at different currents;

[0035] Fig. 9 This is the preparation method of the anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention, and the discharge curve diagram of Example 7 at different currents. DETAILED DESCRIPTION

[0036] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0037] The preparation method of the anion-cation doped modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention adopts a metal salt solution, a precipitant, a fluorine source, and a complexing agent to prepare a modified lithium-rich manganese-based precursor, and adopts the modified lithium-rich manganese-based precursor and a lithium source to prepare anion-cation co-doped cobalt-free lithium-rich manganese-based positive electrode material. The metal salt solution contains manganese, nickel, and aluminum; wherein the molar ratio of manganese, nickel, and aluminum is a:b:x, and the molar ratio of fluorine is y; the value ranges of a, b, x, and y are: a>0.5, 0<b≤0.2, 0<x<0.1, and a+b+x=0.8; 0.01≤y≤0.06.

[0038] The preparation method of the anion-cation doped modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention can realize the anion-cation modification of cobalt-free lithium-rich manganese (LNMO) through aluminum salt and fluorine source in metal salt solution. Al doping can adjust the local electronic structure, increase the redox potential, improve the interaction with oxygen, further stabilize the lattice oxygen and inhibit the release of lattice oxygen, make the positive electrode material structure stable, and have good long cycle performance; F doping can induce the formation of the initial spinel phase on the surface of the material, and at the same time inhibit the transformation of the material from the layered to the spinel phase during the cycle process, improve the conductivity of the material ions and electrons, and then improve the rate performance of the material. Al and F are simultaneously modified by anions and cations, and the combination of the two plays a synergistic role, which not only improves the long cycle performance of the original material, but also modifies the rate performance of the material, effectively inhibits the mixed arrangement of lithium nickel cations, improves the stability of the layered structure and the rate performance under the condition of 5C high current, and can better improve the electrochemical performance of lithium-rich layered oxides. Therefore, by using Al doping and F doping at the same time, the voltage decay of the modified positive electrode material can be slowed down and the cycle performance can be excellent, which solves the problems of severe voltage decay and poor cycle stability of the existing cobalt-free lithium-rich manganese-based materials.

[0039] Preferably, the molar ratio x of aluminum is 0.01 to 0.06; more preferably, x is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, etc.

[0040] Preferably, the molar ratio y of fluorine is 0.02, 0.04, 0.06, etc.

[0041] Since the material obtained by the preparation method of the present invention is a modified LNMO, the modified material must contain oxygen elements, and the addition of Li can be set according to various specific optional molar ratios.

[0042] Preferably, in the preparation method of the present invention, the precipitant includes alkali solution, and the complexing agent includes one or more of ammonia water and ammonium bicarbonate.

[0043] More preferably, the alkali solution is one or more of sodium carbonate, sodium bicarbonate and sodium hydroxide.

[0044] Preferably, the lithium source is one or more of lithium hydroxide, lithium sulfide, and lithium carbonate; the aluminum source is one or both of aluminum oxide and aluminum nitrate; and the fluorine source includes one or both of ammonium fluoride and lithium fluoride.

[0045] The preparation method of the present invention comprises the following steps:

[0046] S1. After the complexing agent is dissolved, the metal salt solution, the precipitant and the fluorine source are injected into the bottom liquid in parallel as a base liquid, stirred and heated to carry out a coprecipitation reaction, and after the reaction is completed, the solution is cooled, filtered and dried to obtain a modified lithium-rich manganese-based precursor. The solvent for dissolving the complexing agent can be water.

[0047] A co-precipitation method-high temperature solid phase method is used to synthesize cobalt-free lithium-rich manganese-based positive electrode materials with aluminum doped manganese and fluorine doped oxygen. The synthesis can follow the conventional lithium-rich manganese-based material preparation process. By co-doping aluminum and fluorine elements into the reaction solution, lithium-rich manganese-based materials with excellent electrochemical stability and performance can be obtained without large-scale increase in production processes and links. This method has a wide range of applications.

[0048] Preferably, the above coprecipitation reaction is carried out in a reactor; specifically, a base liquid is added to the reactor, and then a metal salt solution, a precipitant and a fluorine source are injected into the reactor in parallel, at which time a peristaltic pump in the reactor stirs and continuously carries out the coprecipitation reaction.

[0049] The flow rate of the parallel injection is 30-80 ml / min, which specifically means that the metal salt solution, the precipitant and the fluorine source are uniformly and parallelly injected into the reactor at the same speed.

[0050] Preferably, the pH of the coprecipitation reaction is 8 to 9, the reaction temperature in the reactor is 50 to 80° C., and the reaction time is 8 to 16 hours.

[0051] More preferably, the reaction temperature in the reactor is 50°C, 55°C, 60°C, 63°C, 70°C, 77°C, 80°C, etc.

[0052] More preferably, the pH of the coprecipitation reaction is 8, 8.2, 8.5, 8.8 or 9, etc.

[0053] More preferably, the reaction time is 8 h, 9 h, 9.5 h, 10 h, 12 h or 16 h.

[0054] Preferably, after the coprecipitation reaction is completed, the obtained precipitate is dissolved with deionized water, filtered or centrifuged with deionized water, then washed 3 to 6 times with ethanol, and dried in an oven at 60 to 120° C. for 12 to 24 hours.

[0055] S2. The modified cobalt-free lithium-rich manganese-based precursor is mixed with a lithium source and subjected to ball milling treatment, and then sintered.

[0056] Preferably, the mixed ball milling treatment is carried out using a planetary ball mill, and the treatment time is 1 to 3 hours; more preferably, the treatment time is 1 hour, 2 hours, 3 hours, etc.

[0057] Preferably, the sintering includes one stage sintering and two stage sintering in sequence; the holding time of the first stage sintering is 4 to 8 hours at a temperature of 400 to 600°C, and the holding time of the second stage sintering is 8 to 16 hours at a temperature of 750 to 950°C.

[0058] Further preferably, the holding time of one sintering stage is 4h, 4.5h, 5h, 6h, 6.5h, 7h or 8h, etc., and the temperature is 400°C, 450°C, 500°C, 520°C, 600°C, etc.

[0059] Further preferably, the holding time of the second stage sintering is 8h, 8.5h, 10h, 12h, 14h or 16h, etc., and the temperature is 750°C, 800°C, 850°C, 900°C, 950°C, etc.

[0060] The anion-cation doped modified cobalt-free lithium-rich manganese-based positive electrode material of the present invention is prepared by the above method. The chemical formula of the positive electrode material is expressed as Li 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) F y .

[0061] The positive electrode material of the present invention, after being modified by doping Al and F anions and cations, has a slowed voltage decay and excellent cycle performance, thus solving the problems of severe voltage decay and poor cycle stability of the general cobalt-free lithium-rich manganese-based material.

[0062] The lithium-ion battery positive electrode plate of the present invention is prepared by adopting the above-mentioned anion-cation doped and modified cobalt-free lithium-rich manganese-based positive electrode material.

[0063] When the positive electrode material of the present invention is used to prepare a positive electrode sheet, any optional conventional method may be used. In a specific embodiment of the present invention, the preparation method comprises the following steps:

[0064] The active material, conductive agent and binder are mixed and then dissolved in a solvent to obtain a slurry. Aluminum foil is used as a current collector, the slurry is evenly coated on the surface of the current collector, and the lithium ion positive electrode sheet is obtained after drying.

[0065] Among them, the active material is a modified cobalt-free lithium-rich manganese-based material, the binder is one or more of polyvinylidene fluoride, polyacrylic acid, and sodium alginate; the conductive agent is acetylene black, conductive carbon black, Super-P or Ketjen black; the solvent is N-methylpyrrolidone; the mass ratio of the anion- and cation-doped modified cobalt-free lithium-rich manganese-based positive electrode material to the conductive agent and the binder is 70-90:5-20:5-20.

[0066] The lithium ion battery of the present invention has a first cycle capacity of 200-250 mAh.g in the voltage range of 2.0-4.8 V. -1 The discharge specific capacity is 200 cycles at a current density of 0.5C. The working voltage decay of the lithium-ion battery before and after the cycle is significantly slowed down, and the capacity retention rate is greater than 80%.

[0067] When a lithium battery is prepared using the positive electrode sheet of the present invention, any optional conventional method may be used. In a specific embodiment of the present invention, the preparation method comprises the following steps:

[0068] The lithium metal is pressed and cut to prepare the negative electrode. Ethylene carbonate and ethyl methyl carbonate are mixed in a volume ratio of 3:7 to form a carbonate electrolyte with a concentration of 0.1 to 2 mol / L. A commercial polypropylene diaphragm is used as the diaphragm, and the support is nickel foam and a gasket.

[0069] The positive electrode sheet, separator, electrolyte, negative electrode sheet and nickel foam of the lithium-ion battery are assembled in sequence in a glove box, and the lithium-ion battery is manufactured through the processes of pressing and standing.

[0070] The present invention is illustrated below by means of specific examples.

[0071] Example 1

[0072] This embodiment adopts the method of the present invention to prepare a method for preparing anion-cation doped modified cobalt-free lithium-rich manganese-based positive electrode material, comprising the following steps:

[0073] First, manganese sulfate monohydrate, nickel sulfate hexahydrate, and aluminum nitrate nonahydrate were weighed and dissolved in deionized water according to the stoichiometric ratio to obtain a mixed sulfate solution A with a total cation concentration of 2 mol / L.

[0074] Similarly, anhydrous sodium carbonate and ammonium fluoride were weighed and dissolved in deionized water according to the stoichiometric ratio to prepare an alkaline solution with a concentration of 2 mol / L to obtain solution B.

[0075] Prepare 20 ml of 0.1 mol / L ammonium bicarbonate solution as the base solution, inject it into a round-bottom flask, and keep it in a water bath at 55°C for later use.

[0076] Then, solution A and solution B were injected into a round-bottom flask containing ammonium bicarbonate (nitrogen was introduced throughout the reaction to prevent oxidation) at a rate of 20 ml / h using a syringe pump, and stirred continuously at 55°C. During the reaction, the pH of the solution was maintained at 8-9. After the feeding was completed, the reaction was continued for 12 hours. After the reaction was completed, it was allowed to stand for 12 hours. Then the supernatant of the product was poured out, and the precipitate was centrifuged three times with deionized water and ethanol, each time at a speed of 7500 r / min, to remove impurity ions such as sodium ions, sulfate ions, and ammonium ions. Dry in a vacuum drying oven at 60°C for 12 hours to obtain a flesh-colored carbonate precursor powder.

[0077] Finally, the precursor powder was mixed with 5% excess lithium carbonate in a molar ratio and ball-milled for 2 h. The mixed sample was calcined at 500 °C for 5 h and at 900 °C for 12 h in a tube furnace at a heating rate of 5 °C / min to obtain a lithium-rich manganese-based positive electrode material Li 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) F y .

[0078] Example 2

[0079] The anion-cation doped modified cobalt-free lithium-rich manganese-based cathode material Li 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) F y , x=0.01, y=0.

[0080] The preparation process of this embodiment is different from that of Embodiment 1 in that in step S1, the manganese sulfate salt, nickel sulfate salt, aluminum nitrate salt, and ammonium fluoride need to be mixed in the corresponding stoichiometric proportions of the required components determined by the cobalt-free lithium-rich manganese-based chemical formula of Embodiment 2.

[0081] Example 3

[0082] The anion-cation doped modified cobalt-free lithium-rich manganese-based cathode material Li 1.2 Mn (0.6-x) Al x Ni 0.2O (2-y) F y , x=0.02, y=0.

[0083] The preparation process of this embodiment is different from that of Embodiment 1 in that in step S1, manganese sulfate salt, nickel sulfate salt, aluminum nitrate salt, and ammonium fluoride need to be mixed in the corresponding stoichiometric proportions of the required components determined by the cobalt-free lithium-rich manganese-based chemical formula described in Embodiment 3.

[0084] Example 4

[0085] The anion-cation doped modified cobalt-free lithium-rich manganese-based cathode material Li 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) F y , x=0.03, y=0.

[0086] The preparation process of this embodiment is different from that of Embodiment 1 in that in step S1, the manganese sulfate salt, nickel sulfate salt, aluminum nitrate salt, and ammonium fluoride need to be mixed in the corresponding stoichiometric proportions of the required components determined by the cobalt-free lithium-rich manganese-based chemical formula described in Embodiment 4.

[0087] Example 5

[0088] The anion-cation doped modified cobalt-free lithium-rich manganese-based cathode material Li 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) F y , x=0.02, y=0.02.

[0089] The preparation process of this embodiment is different from that of Embodiment 1 in that in step S1, the manganese sulfate salt, nickel sulfate salt, aluminum nitrate salt, and ammonium fluoride need to be mixed in the corresponding stoichiometric proportions of the required components determined by the cobalt-free lithium-rich manganese-based chemical formula described in Embodiment 5.

[0090] Example 6

[0091] The anion-cation doped modified cobalt-free lithium-rich manganese-based cathode material Li 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) F y , x=0.02, y=0.04.

[0092] The preparation process of this embodiment is different from that of Embodiment 1 in that in step S1, manganese sulfate salt, nickel sulfate salt, aluminum nitrate salt, and ammonium fluoride need to be mixed in the corresponding stoichiometric proportions of the required components determined by the cobalt-free lithium-rich manganese-based chemical formula described in Embodiment 6.

[0093] Example 7

[0094] The anion-cation doped modified cobalt-free lithium-rich manganese-based cathode material Li 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) F y , x=0.02, y=0.06.

[0095] The preparation process of this embodiment is different from that of Embodiment 1 in that in step S1, manganese sulfate salt, nickel sulfate salt, aluminum nitrate salt, and ammonium fluoride need to be mixed in the corresponding stoichiometric proportions of the required components determined by the cobalt-free lithium-rich manganese-based chemical formula described in Embodiment 7.

[0096] Meanwhile, the positive electrode material of this embodiment is used to prepare the positive electrode sheet, and the mass ratio of the positive electrode material to the binder is 8:1, and the mass ratio of the positive electrode material to the conductive agent is 8:1.

[0097] The binder is polyvinylidene fluoride, the solvent is N-methylpyrrolidone, the conductive agent is Super-P, the support is nickel foam, and the electrolyte is a carbonate electrolyte with a volume ratio of 3:7 and a concentration of 1 mol / L.

[0098] Example 8

[0099] In this embodiment, the positive electrode material is prepared by the method of embodiment 1. The material is not doped with Al and F. The other steps are the same as those of embodiment 1. The obtained material is Li 1.2 Mn 0.6 Ni 0.2 O2.

[0100] The performance of the positive electrode materials obtained in the above embodiments was tested and compared, and the following results were obtained:

[0101] (1) Figure 1 The PXRD patterns of the materials of Example 8, Example 3 and Example 7 are shown in Figure 1. Example 8 is a non-doped modified Li 1.2 Mn 0.6 Ni 0.2 O2, Example 3 is Li doped with Al only 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) Fy (x=0.02, y=0), Example 7 is Al and F doped Li 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) F y (x=0.02, y=0.06).

[0102] according to Figure 1 It can be seen that all samples have obvious layered structural characteristics and no visible impurities. And the main diffraction peak belongs to the R-3m space group of the layered LiMO2 phase. This shows that the desired LNMO material can be prepared by the method of the present invention regardless of whether doping is performed.

[0103] (2) Figures 2 to 4 The SEM images of the materials of Example 8, Example 3 and Example 7 are shown respectively. Figures 2 to 4 By comparison, it can be found that the surface roughness of the unmodified Example 8 material is significantly more serious. This is because there is no other anion supplement during the secondary sintering process, resulting in excessive oxygen deficiency. After doping, the surface is smooth again, indicating that F can replace the position of O, thereby inhibiting the material structure damage caused by O loss.

[0104] (3) Figure 5 : is a comparison chart of the cycle performance of the materials of Example 8, Example 3 and Example 7. Figure 5 It can be seen that after doping, the cycle stability of the material is significantly improved.

[0105] (4) Figure 6 This is a comparison chart of the first cycle charge and discharge of the materials of Example 8, Example 3 and Example 7. Figure 6 It can be seen that all samples exhibit the characteristics of lithium-rich positive electrode materials, and the first-cycle charge and discharge specific capacity of the double-modified materials is significantly increased.

[0106] (5) Figure 7 This is a comparison chart of the rate performance of the materials of Example 8, Example 3 and Example 7. Figure 7 It can be seen that the double-modified samples show good rate performance at different rates. At high currents of 2C and 5C, the capacity of the modified samples is more obvious and decays slowly.

[0107] (6) Figure 8 The discharge curves of Example 8 at different currents are as follows: Fig. 9 2 is a discharge curve diagram of Example 7 at different currents.

[0108] contrast Figure 8 and Fig. 9It can be seen that the voltage attenuation of the modified sample is significantly alleviated.

[0109] In summary, the cobalt-free lithium-rich manganese-based positive electrode material was modified through a simple and effective fluorine-aluminum co-doping method, and the discharge capacity and cycle stability of the material were improved. At the same time, the comparison results showed that the modified material had better rate performance, higher cycle capacity retention rate, and less voltage attenuation.

[0110] In the description of the present invention, it should be noted that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0111] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0112] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0113] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0114] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an anion- and cation-doped modified cobalt-free lithium-rich manganese-based positive electrode material, characterized in that: A modified lithium-rich manganese-based precursor is prepared by using a metal salt solution, a precipitant, a fluorine source, and a complexing agent, and the anion-cation co-doped cobalt-free lithium-rich manganese-based positive electrode material is prepared by using the modified lithium-rich manganese-based precursor and a lithium source; the metal salt solution contains manganese salt, nickel salt, and aluminum salt; The molar ratio of manganese, nickel, aluminum and fluorine is a:b:x:y; the value ranges of a, b, x and y are: a>0.5, 0<b≤0.2, 0<x<0.1, and a+b+x=0.8; 0.01≤y≤0.

06.

2. The method for preparing a cobalt-free lithium-rich manganese-based positive electrode material modified by anion and cation doping according to claim 1, characterized in that: The precipitant includes alkali solution, and the complexing agent includes one or more of ammonia water and ammonium bicarbonate.

3. The method for preparing a cobalt-free lithium-rich manganese-based positive electrode material modified by anion and cation doping according to claim 1, characterized in that: The lithium source is one or more of lithium hydroxide, lithium sulfide, and lithium carbonate; the aluminum salt is one or both of aluminum oxide and aluminum nitrate; and the fluorine source includes one or both of ammonium fluoride and lithium fluoride.

4. The method for preparing a cobalt-free lithium-rich manganese-based positive electrode material modified by anion and cation doping according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, after dissolving the complexing agent, the metal salt solution, the precipitant and the fluorine source are injected into the base liquid in parallel as a base liquid, stirred and heated to carry out a coprecipitation reaction, and after the reaction is completed, cooled, filtered and dried to obtain the modified lithium-rich manganese-based precursor; S2, mixing the modified cobalt-free lithium-rich manganese-based precursor with the lithium source, subjecting the mixture to ball milling treatment, and then sintering the mixture.

5. The method for preparing a cobalt-free lithium-rich manganese-based positive electrode material modified by anion and cation doping according to claim 4, characterized in that: In step S1, the flow rate of the parallel flow injection is 30-80 ml / min.

6. The method for preparing a cobalt-free lithium-rich manganese-based positive electrode material modified by anion and cation doping according to claim 4, characterized in that: In step S1, the pH of the coprecipitation reaction is 8-9, the reaction temperature is 50-80° C., and the reaction time is 8-16 hours.

7. The method for preparing a cobalt-free lithium-rich manganese-based positive electrode material modified by anion and cation doping according to claim 4, characterized in that: In step S2, the sintering includes one stage sintering and two stage sintering in sequence; the holding time of the one stage sintering is 4 to 8 hours at a temperature of 400 to 600°C, and the holding time of the two stage sintering is 8 to 16 hours at a temperature of 750 to 950°C.

8. An anion- and cation-doped modified cobalt-free lithium-rich manganese-based positive electrode material, characterized in that: Prepared by the method according to any one of claims 1 to 7; the chemical formula of the positive electrode material is Li 1.2 Mn (0.6-x) Al x Ni 0.2 O (2-y) F y .

9. A positive electrode plate for a lithium-ion battery, characterized in that: It is prepared by using the anion- and cation-doped modified cobalt-free lithium-rich manganese-based positive electrode material as described in claim 8.

10. A lithium ion battery, characterized in that: Comprising the lithium-ion battery positive electrode plate as claimed in claim 9.

Citation Information

Patent Citations

  • Cr3&lt;+&gt;, Al&lt;3+&gt;, Fe&lt;3+&gt; and F &lt;-&gt; co-doped composite lithium-rich anode material and preparation method thereof

    CN103078103A

  • Modified lithium nickel manganese oxygen material, preparation method of modified lithium nickel manganese oxygen material, and lithium ion battery

    CN104425810A

  • Synthesis of novel negative and positive ions Cl and Al-codoped modified rich-lithium layered positive electrode material

    CN105895902A

  • High-voltage spinel type lithium ion battery positive electrode material doped by anion and cation and preparation method thereof

    CN108091854A

  • Negative and positive ion co-doped modified lithium ion battery positive material and preparation method thereof

    CN110323432A

Cited By

  • Composite positive electrode material, all-solid-state battery and charging and discharging method of all-solid-state battery

    CN120809800A

  • Cobalt-free lithium-rich manganese-based positive electrode material and preparation method thereof

    CN120895627A